ENT300 - Fundamentals of Entrepreneurship SIDEOUT / Mohamad Amizan Shafiq Azmi... [et.al] - Azmi, Mohamad Amizan Shafiq; Mulok, Abdul Arif; Sapuan, Mohd Arif; Akil, Amirul (2015)
Our company name is SIDEOUT. We have decided to form a partnership business. Each partner has contributed certain amount of capital as agreed in our agreement. Our main business is selling sport shoes, stocking and pad. We also will give the good quality products to our customers to ensure the satisfied with our sevices and products. We will open our sports shoes center at Level 1 Summer Mall, Jalan Dato' Mohd Musa, Kota Samarahan Sarawak. All partners are encourage and entitled to participate in all business management. We have agreed that Mohamad Amizan Shafiq bin Azmi as the General Manager and Administration Manager. Mohd Arif bin Sapuan will be the Operational Manager, Abdul Arif bin Mulok will be the Marketing Manager and Amirul bin Akil will be the Financial Manager. The management team will be leads by the General Manager and will be help by the other managers in other process. The general manager is responsible in controlling, leading, organizing as well as planning the entire business. The administrative manager will responsible in doing all jobs relating to office administration. The marketing manager will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operation of our business is controlled and monitored by the operation manager. This is where quality control and productivity will take place in order to improve the efficiency of the workers. Finally, the financial manager will handle the financial matters such as preparing for the budgets and financial statement for the each department. All the financial statement need to be taken care properly by our Finance Manager.